Mutual city/state weather forecasting by ANN and HMM – Survey - Acharya, Unnati; Sahani, G.J (International Journal of Computer Sciences and Engineering, 2025)
Weather forecasting is an important apply for in meteorology and has been one of the most scientifically and technologically difficult problems around the world. Weather prediction approaches are challenged by difficult weather phenomena with incomplete explanation and past data. Weather phenomena have many parameters that are impossible to enumerate and measure. Increasing development on statement systems enabled weather forecast expert systems to combine and divide resources and thus hybrid system has emerged. Even though these improvements on weather forecast, these expert systems can’t be fully reliable since weather forecast is main problem. A predictive Neural Network model and Hidden Markov Model was also residential for the weather prediction program and the outcome compared with real weather data for the predicted periods. The results show that given enough case data, Data Mining techniques can be used for weather forecasting and climate change studies. Data mining is a process that uses a variety of data analysis tools to find out patterns and relationships in data that may be used to create applicable prediction. The proposed ANN and HMM evaluates the presentation of the developed models by applying unusual neurons, hidden layers and transfer functions to predict temperature for 365 days of the year. The criteria used for suitable model selection is mean square error (MSE).